2020
DOI: 10.3390/min10100872
|View full text |Cite
|
Sign up to set email alerts
|

Development of Porous Asphalt with Bitumen Emulsion, Electric arc Furnace Slag and Cellulose Fibers for Medium Traffic Roads

Abstract: The construction of road infrastructure is one of the most polluting activities that exists today. Therefore, the use of waste from other industries is an excellent solution, since it reduces the consumption of raw materials, reduces CO2 emissions and avoids the disposal of waste in a landfill. In this study, electric arc furnace slag, cellulose fibers from the papermaking industry and bitumen emulsion were used for the conformation of sustainable and porous bituminous mixtures. Electric arc furnace slag was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…This has demonstrated the cementitious properties of ladle furnace slag [28]. Accordingly, this waste has interesting particularities for its use as a filler in bituminous mixtures [29][30][31]. However, it is necessary to carry out a chemical characterization to determine which compounds are pollutants or harmful to the final product; and a physical characterization must be carried out to corroborate that it does indeed have the appropriate properties for use as a filler.…”
Section: Of 15mentioning
confidence: 99%
“…This has demonstrated the cementitious properties of ladle furnace slag [28]. Accordingly, this waste has interesting particularities for its use as a filler in bituminous mixtures [29][30][31]. However, it is necessary to carry out a chemical characterization to determine which compounds are pollutants or harmful to the final product; and a physical characterization must be carried out to corroborate that it does indeed have the appropriate properties for use as a filler.…”
Section: Of 15mentioning
confidence: 99%
“…Electric arc furnace slags have been used as building materials in different investigations, and even in real cases [18,19]. The electric arc furnace slags have been used as an aggregate for hot mix asphalt [20,21], warm mix asphalt [22] and even for mixes with bituminous emulsion [23]; this shows its excellent mechanical characteristics and its use in developing high quality bituminous mixtures [24]. However, in most cases the characteristics of this by-product have not been maximized and its use has been relegated to low-level materials [25].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, and with the aim of reducing the extraction of raw materials, waste has been reused for the formation of bituminous mixtures. These wastes include scrap tires [21], mining waste [22,23], ceramic waste [24], recycled concrete aggregate [25], steel slags [26][27][28], recycled glass [29], etc. Most of the investigations concluded that a detailed study of the physical, chemical, and mechanical properties of the wastes, as well as a thorough knowledge of the bituminous mixes, led to end products of similar quality to those made with conventional materials and techniques.…”
Section: Introductionmentioning
confidence: 99%